A Case of Renal Cell Carcinoma and Pheochromocytoma Due to Germline Inactivating Mutation in Fumarate Hydratase (FH) - Reda, Sarah Alicia (J Endocr Soc, 2021)
A 60-year-old female with a history of well-controlled hypertension, prediabetes, status post hysterectomy for fibroids, presented for evaluation of hematuria and unintentional weight loss. She denied palpitations, headaches, tremors, and diaphoresis. Initial CT demonstrated a right renal mass suspicious for renal cell carcinoma and an adrenal mass. Magnetic resonance imaging (MRI) confirmed a hypervascular, right adrenal mass (6.7 x 6 x 5 cm) without loss of signal. Laboratory Testing: elevated 24-hour urine vanillylmandelic acid (VMA) 17.5 mg/24 h (<6), and urine normetanephrines 2276 ug/24 h (122-676) with normal urine metanephrines 158 ug/24 h (90-315). 24-hour urine free cortisol was normal. The patient underwent a right adrenalectomy and partial nephrectomy. Pathology confirmed a low-grade renal cell carcinoma (RCC) and a 6.8 cm pheochromocytoma (PCC). Genetic analysis revealed an inherited mutation in the fumarate hydratase (FH) gene, which is diagnostic of hereditary leiomyomatosis and renal cell cancer (HLRCC). Wildtype FH codes for an enzyme that converts fumarate to malate in the mitochondrial Krebs cycle. Inactivating mutations in FH trigger the hypoxia pathway by activating hypoxia-inducible factor (HIF) thereby promoting tumor growth and angiogenesis. In PCC, 30-40% are hereditary and another 40-50% are found to have somatic mutations in 1 of 20 PCC susceptibility genes. Several autosomal dominant heritable syndromes, including Neurofibromatosis type 1 (NF-1), von Hippel-Lindau (VHL), Multiple Endocrine Neoplasia Type 2 (MEN 2), and Paraganglioma Syndromes Types 1–5, have an increased incidence of PCC, most of which modulate hypoxia pathways. FH mutations are similarly inherited in an autosomal dominant fashion and cause HLRCC. HLRCC is associated with 75-80% risk for cutaneous and uterine leiomyomas, and a 10-16% risk for type II papillary renal cell carcinoma. The risk of RCC in patients with FH mutations is much greater than in the general population, where the prevalence is ~2% in those who lack the mutation. In one study, FH deficiencies attribute between 19-41% of all RCC cases. Rare families with PGL/PCC have also been found to carry this germline FH mutation. This FH mutation is associated with increased risk of metastasis in patients with PGL/PCC by a similar mechanism of carcinogenesis via the hypoxia pathway. Currently, there are no strict guidelines for surveillance in individuals with HLRCC, however, patients should have a yearly abdominal MRI, skin examination every 2 years, and an annual gynecological evaluation for leiomyosarcoma. Each first-degree relative should be offered genetic testing of the FH mutation, as 50% of relatives may carry the gene. This case underscores the importance of genetic workups in patients with PCC, especially if associated with other tumors.